Eksistensi Dan Urgensi Pendidikan Karakter - Niken Ristianah (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2020)
The moral decadence that continues to burn and the values ​​of goodness that actors of religious, national and state life begin to ignore, anyone anywhere and anytime can be hurt by their cruelty. Family, school and community consciously or unconsciously contribute to what happens. Character education is a conscious effort in shaping a person's personality through character education, the results of which can be seen in real action, even though this is not easy because it involves one's habits, but it does not rule out the possibility that this can be done as well as possible. Several character education methods that can be applied in family, school, and community, namely: exemplary, discipline, habituation, creating a conducive atmosphere, integration and internalization. Character education values ​​consist of: religious values, honesty, tolerance, discipline , hard work, creative, independent, democratic, curiosity, national spirit, love of the country, respect for achievement, friendly/communicative, love peace, love to read, care about social, care for the environment, and the responsibility, which are those values ​​come from the basics: sources of Religion, Pancasila, Culture, and National Education Objectives.